Comparative Analysis of Specifications for the Construction of Robotic and Non-Robotic Operating Rooms in Hospitals in Jakarta - Verell Rengga Harsvardan; Wati Asriningsih Pranoto; Mark Setiadi (Green Publisher Indonesia, 2025)
Technological developments in the health sector, especially in surgery, have encouraged hospitals to adopt robotic-based operating systems. The use of robotic surgery provides clinical benefits such as increased precision, 3D visualization, and faster patient recovery. However, the adoption of this technology requires the support of significantly different operating room infrastructure compared to conventional operating rooms. This study aims to conduct a systematic review of the literature that compares the specifications of robotic and non-robotic operating room construction, focusing on design aspects, mechanical-electrical systems, and construction costs. The method used is Systematic Literature Review (SLR) based on the PRISMA protocol, with data sources from Scopus, ScienceDirect, PubMed, and Google Scholar databases. A total of 25 scientific articles that met the inclusion criteria were analyzed qualitatively. The results of the study showed that robotic operating rooms require a larger area (≥60 m²), Laminar Air Flow (LAF) ventilation systems, additional radiation protection, as well as more complex electrical systems such as HMI and UPS. In addition, the cost of building a robotic operating room is reportedly much higher compared to a non-robotic room. The study also identifies the limitations of the literature in Indonesia that discusses the technical planning of robotic operating rooms, thus providing opportunities for further research in the field of health facility design. The results of this study are expected to be a reference for hospitals, construction planners, and policymakers in developing advanced technology-based operating room infrastructure.